Temperature‐Dependent Electronic Ground‐State Charge Transfer in van der Waals Heterostructures. Issue 29 (25th May 2021) - Park, Soohyung; Wang, Haiyuan; Schultz, Thorsten; Shin, Dongguen; Ovsyannikov, Ruslan; Zacharias, Marios; Maksimov, Dmitrii; Meissner, Matthias; Hasegawa, Yuri; Yamaguchi, Takuma; Kera, Satoshi; Aljarb, Areej; et al.
Abstract: Electronic charge rearrangement between components of a heterostructure is the fundamental principle to reach the electronic ground state. It is acknowledged that the density of state distribution of the components governs the amount of charge transfer, but a notable dependence on temperature is not yet considered, particularly for weakly interacting systems. Here, it is experimentally observed that the amount of ground‐state charge transfer in a van der Waals heterostructure formed by monolayer MoS2 sandwiched between graphite and a molecular electron acceptor layer increases by a factor of 3 when going from 7 K to room temperature. State‐of‐the‐art electronic structure calculations of the full heterostructure that accounts for nuclear thermal fluctuations reveal intracomponent electron–phonon coupling and intercomponent electronic coupling as the key factors determining the amount of charge transfer. This conclusion is rationalized by a model applicable to multicomponent van der Waals heterostructures. Abstract : The amount of charge transfer between components of a van der Waals heterostructure to reach the electronic ground state can exhibit a strong temperature dependence. For a donor–bridge–acceptor‐type heterostructure, the intra component electron–phonon coupling and the intercomponent electronic coupling result in a temperature‐dependent density of states available for charge transfer.